Trends in blood pressure, blood lipids, and smoking from 259 753 patients with hypertension in a Swedish primary care register: results from QregPV. (31st May 2021) - Bager, Johan-Emil; Mourtzinis, Georgios; Andersson, Tobias; Nåtman, Jonatan; Rosengren, Annika; Björck, Staffan; Manhem, Karin; Hjerpe, Per
Abstract: Aims: To describe 8-year trends in blood pressure (BP) control, blood lipid control, and smoking habits in patients with hypertension from QregPV, a primary care register in the Region of Västra Götaland, Sweden. Methods and results: QregPV features clinical data on BP, low-density lipoprotein cholesterol (LDL-C), and smoking habits in 392 277 patients with hypertension or coronary heart disease or diabetes mellitus or any combination of the three diagnoses. Data from routine clinical practice have been automatically reported on a monthly basis to QregPV from all primary care centres in Västra Götaland (population 1.67 million) since 2010. Additional data on diagnoses, dispensed drugs and socioeconomic factors were acquired through linkage to regional and national registers. We identified 259 753 patients with hypertension, but without coronary heart disease and diabetes mellitus, in QregPV. From 2010 to 2017, the proportion of patients with BP <140/90 mmHg increased from 38.9% to 49.1%, while the proportion of patients with LDL-C <2.6 mmol/L increased from 19.7% to 21.1% and smoking decreased from 15.7% to 12.3%. However, in 2017, only 10.0% of all patients with hypertension had attained target levels of BP <140/90 mmHg, LDL-C < 2.6 mmol/L while being also non-smokers. The remaining 90.0% were still exposed to at least one uncontrolled, modifiable risk factor for cardiovascular disease. Conclusions: These regionwide data from eight consecutive years in 259 753 patients with hypertension demonstrate a large potential for risk factor improvement. An increased use of statins and antihypertensive drugs should, in addition to lifestyle modifications, decrease the risk of cardiovascular disease in these patients.